At-Tashbīh fī Khuṭub Khulafā’ ar-Rāshidīn (Dirāsah Balāghiyyah Bayāniyyah): At-Tashbīh in the Sermons of the Rightly Guided Caliphs (A Rhetorical and Expository Study) - Zaki, Muhammad; Setyo Rini, Fitri; Ali Ridho, Arsyad Muhammad; Muhammad Wahyudi (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2024)
This article presents a rhetorical and illustrative study of similes in the speeches of the Rashidun Caliphs, highlighting the use of similes as a prominent rhetorical tool employed by the caliphs to enhance meanings and clarify ideas. The article reviews various types of similes and their usage in different contexts to effectively convey messages. The research aims to explore the aesthetic and communicative effectiveness of these rhetorical devices in conveying profound meanings and engaging the audience. Utilizing a library research method, the study meticulously examines historical texts, analyzing the frequency, context, and stylistic nuances of similes used by the Caliphs. The findings reveal a rich tapestry of similes that not only enhance the eloquence of the speeches but also serve to clarify complex ideas, reinforce moral teachings, and evoke emotional responses from listeners. This research highlights the enduring impact of these rhetorical strategies on Islamic oratory and their contribution to the persuasive power of the Caliphs' speeches. In conclusion, the study underscores the significance of similes in Islamic rhetorical tradition, demonstrating their role in shaping the legacy of the Rightly Guided Caliphs' discourse. قدم هذه المقالة دراسة بلاغية وبيانية للتشبيهات في خطب خلفاء الرّاشدين، مسلطة الضوء على استخدام التشبيهات كأداة بلاغية بارزة استخدمها الخلفاء لتعزيز المعاني وتوضيح الأفكار. تستعرض المقالة أنواع التشبيهات المختلفة واستخدامها في سياقات متنوعة لتوصيل الرسائل بفعالية. تهدف هذه الدراسة إلى استكشاف الفعالية الجمالية والتواصلية لهذه الأدوات البلاغية في نقل المعاني العميقة وجذب انتباه الجمهور. باستخدام منهج البحث المكتبي، تفحص الدراسة بشكل دقيق النصوص التاريخية، محللةً تكرار التشبيهات وسياقها وفروقها الأسلوبية التي استخدمها الخلفاء. تكشف النتائج عن نسيج غني من التشبيهات التي لا تعزز فقط بلاغة الخطب ولكنها أيضًا تخدم في توضيح الأفكار المعقدة وتعزيز الدروس الأخلاقية واستثارة الاستجابات العاطفية من المستمعين. تسلط هذه الدراسة الضوء على التأثير المستمر لهذه الاستراتيجيات البلاغية على الخطابة الإسلامية ومساهمتها في القوة الإقناعية لخطب الخلفاء. في الختام، تؤكد الدراسة على أهمية التشبيهات في التقليد البلاغي الإسلامي، موضحةً دورها في تشكيل إرث خطب الخلفاء الراشدين. Artikel ini menyajikan studi retorika dan ilustratif tentang simile dalam pidato para Khalifah Rasyidin, menyoroti penggunaan simile sebagai alat retorika utama yang digunakan oleh para khalifah untuk memperkuat makna dan memperjelas ide. Artikel ini mengulas berbagai jenis simile dan penggunaannya dalam konteks yang berbeda untuk menyampaikan pesan secara efektif. Penelitian ini bertujuan untuk mengeksplorasi efektivitas estetika dan komunikatif dari perangkat retorika ini dalam menyampaikan makna yang mendalam dan melibatkan audiens. Dengan menggunakan metode penelitian kepustakaan, studi ini dengan cermat meneliti teks-teks sejarah, menganalisis frekuensi, konteks, dan nuansa gaya dari simile yang digunakan oleh para Khalifah. Temuan penelitian mengungkapkan kekayaan simile yang tidak hanya meningkatkan keindahan pidato, tetapi juga berfungsi untuk memperjelas ide-ide kompleks, memperkuat ajaran moral, dan memancing respons emosional dari para pendengar. Penelitian ini menyoroti dampak berkelanjutan dari strategi retorika ini pada orasi Islam dan kontribusinya terhadap kekuatan persuasif pidato para Khalifah. Sebagai kesimpulan, studi ini menegaskan pentingnya simile dalam tradisi retorika Islam, menunjukkan perannya dalam membentuk warisan pidato para Khalifah Rasyidin.